Syndicated Lending Relationships, Information Asymmetry, and Market Making in the Secondary Loan Market - PHILLIPS, MATTHEW A. (Journal of Accounting Research, 2025)
ABSTRACT This paper investigates why commercial lenders make markets for the loans that they sell on the secondary market. Using loan‐level data, I find that origination lenders with extensive borrower relationships and more reputational capital at stake are more likely to serve as market makers. Greater participation of origination lenders as market makers is associated with lower trading costs for their borrowers' loans. This association remains even in conditions where origination lenders could exploit their information advantage for market making profits. Lenders benefit from being market makers by maintaining strong subsequent lending relationships with their borrowers. Collectively, this evidence is consistent with origination lenders' participation in the secondary market being motivated by reducing trading frictions rather than market making profits.